International investment instruments : a compendium - United Nations. Conference on Trade and Development (Geneva United Nations, 2000)
Multilateral instruments-v.1 Regional instruments-v.2 Regional integration, bilateral and non-governmental instruments-v.3 Multilateral and regional instruments-v.4 Regional integration, bilateral and non-governmental instruments-v.5 Bilateral instruments, prototype instruments-v.10
Keywords: Acuerdos Multilaterales; Inversiones; Integracion Regional; Libre Comercio; Tratados Comerciales